The influence of the LSLC-based GIL learning model on the material of electrolysis cells on the learning outcomes of class XII students of SMA N 5 Padang - Rahil Ramadani; Andromeda Andromeda; Yemmi Suriati (Jurnal Pendidikan Kimia (JPKim), 2022)
This research is motivated by the not optimal learning model used by educators. To overcome this problem, a Lesson Study for Learning Community (LSLC) is implemented, there are 3 stages (Plan, Do and See) in one cycle. The role of the observer in the LSLC will have an impact on increasing the competence of educators, which will affect the learning process and increase student learning outcomes. The purpose of the study was to determine the effect of the LSLC-based Guided Inquiry Learning Model on the Electrolysis Cell material on the learning outcomes of class XII students of SMA N 5 Padang. The type of research is Quasi Experiment with Pretest-Posttest Control Group Design. The study population was class XII students of SMA N 5 Padang and samples of class XII MIPA 1 and XII MIPA 3. Data were analyzed using the N-gain test, normality test, homogeneity test, and hypothesis testing (t-test). Based on the results of the study, the influence of the LSLC-based Guided Inquiry Learning (GIL) learning model, the results of the N-gain value analysis (g = 0.63) stated that the LSLC-based GIL learning model had moderate criteria. This shows that the LSLC-based GIL learning model is effective in improving student learning outcomes. This is evidenced by the increase in learning outcomes by 32.97%, the sample data is normally distributed, the two research samples are homogeneous, the hypothesis test is obtained tcount (2.04) and ttable (1.994), it can be concluded that Ho is rejected because tcount is greater than ttable.Keywords:Electrolysis cells, GIL, LSLC, Learning Outcomes